THE ROLE OF PARADIPLOMACY AND THE POTENTIAL PROTO-DIPLOMACY IN THE UNITARY STATE - Laode Muhamad Fathun (Journal of Islamic World and Politics, 2022)
This article aims to explain the study of paradiplomacy in the unitary state. With the case study of Indonesia, the author explains the role of paradiplomacy and the potential of proto-diplomacy in a unitary state like Indonesia. This article uses a qualitative method with a case study method with research data sources, journal articles, books, reports and other relevant sources. The results found that the role of paradiplomacy in Indonesia is still conservative because it still follows the boundaries that have been set. Post-reform the role of paradiplomacy is very stretched, especially in big cities such as Jakarta, Bandung, Surabaya, which already have strategic partners abroad. This role opens up opportunities for cooperation in economic, social, cultural, educational and other fields that are needed by para-diplomacy. The role of paradiplomacy has been stated in various regulations as the basic foundation for moving in search of strategic partners abroad. Although it has a positive impact, it turns out that there is potential for proto-diplomacy in Indonesia. This is especially the case for areas that have a history of popular movement for regional independence. This movement has the potential to lead to disintegration. However, it can be muted if each party can reduce ego and commitment to build together.